Influence of capacity building and barriers on economic empowerment among youth in Abuja, Nigeria - Obinna, Amadi Bede (2012)
The informal sector of Nigeria has become a growing source of economic empowerment for the unemployed youth. Using the Vocational Skills Development model of Nigeria’s National Directorate of Employment, the study illustrates the effectiveness of skills training (capacity building) as a valuable community development strategy of promoting economic empowerment and self employment among the unemployed Nigerian youth. The study employed a quantitative approach using questionnaire survey which was self-administered to a sample size of 268 participants, who were aged 19 to 35 years. They were trained under the above skills development scheme and are presently either selfemployed or wage-employed (in the case of those yet to establish their personal businesses). Insightful information through focus group discussions complemented the designing of some research instruments by the researcher,which include perceived skill acquisition scale, perceived economic wellbeing scale and barriers to economic empowerment measure. Other research scales were either used in their original or modified version. The data collected were quantitatively analyzed using Statistical Package for the Social Sciences; while inferential statistics and multiple regression were used as techniques for analysis. Findings from the analysis revealed that capacity building resulted in economic empowerment of the youth. The study also found that barriers to economic empowerment showed significant influence on participants’ economic wellbeing, such that the more the participants experience the barriers the less their economic empowerment. The moderation effect of barriers reduced the significant positive relationship between capacity building components and economic empowerment when it is at a high level. Since poverty among Nigerian youth is manifested in unemployment, the training has proved to be a useful community development strategy of unemployment reduction through job creation, improved livelihood, and economic independence among the youth. However, to achieve a more successful result among the youth the researcher proffered a list of recommendations to policy makers, such as providing financial services and enabling infrastructure for the youth.